1994
DOI: 10.1161/01.cir.90.6.2899
|View full text |Cite
|
Sign up to set email alerts
|

End-systolic volume and long-term survival after coronary artery bypass graft surgery in patients with impaired left ventricular function.

Abstract: End-systolic volume index is the major predictor of survival after coronary artery bypass graft surgery in patients with impaired left ventricular function. Strategies to prevent ventricular dilatation, such as angiotensin-converting enzyme inhibitors, may improve the long-term outcome in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
56
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(60 citation statements)
references
References 42 publications
4
56
0
Order By: Relevance
“…In patients who had a preoperative LVESVI of 100 mL/m 2 or less, we observed a favorable outcome for survival and the recovery of left ventricular function. That finding supports the conclusion of other investigators [23,24] who noted that the LVESVI was the only independent measurement that was predictive of survival and the improvement of left ventricular function. The LVESVI is a simple and noninvasive preoperative predictor of postoperative functional recovery.…”
Section: Predictors Of Late Outcomesupporting
confidence: 91%
“…In patients who had a preoperative LVESVI of 100 mL/m 2 or less, we observed a favorable outcome for survival and the recovery of left ventricular function. That finding supports the conclusion of other investigators [23,24] who noted that the LVESVI was the only independent measurement that was predictive of survival and the improvement of left ventricular function. The LVESVI is a simple and noninvasive preoperative predictor of postoperative functional recovery.…”
Section: Predictors Of Late Outcomesupporting
confidence: 91%
“…Risk stratification in patients with LV ischemic dysfunction typically includes a combination of clinical, hemodynamic, and angiographic parameters. 17 Recent studies using myocardial metabolic imaging with positron emission tomography (PET) have indicated that assessing myocardial viability also provides useful prognostic information in these patients, [17][18][19][20][21] with an effect additive to that of the usual clinical assessment. 21 Whereas PET is expensive and not widely available, exercise-redistribution-reinjection thallium scintigraphy and dobutamine echocardiography are less expensive and potentially more widely available methods that can also distinguish viable from nonviable myocardium.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, many other studies, including the present one, demonstrate improved LVEF, functional status, and quality of life, as well as decreased ventricular size, even in long-term follow-up, for patients treated with CABG, which implies reverse remodeling of the failing heart. 9,13,[16][17][18] …”
Section: Discussionmentioning
confidence: 99%